PENGARUH ASUPAN GIZI SEBELUM HAMIL DAN USIA IBU HAMIL DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER II - Endah Kusumawati; Suhartik (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Anemia in pregnancy is a global health problem that risks increasing maternal and fetal morbidity and mortality. A preliminary study in Mojo Village showed a high prevalence of pregnant women with anemia. This study analyzed the effect of pre-pregnancy nutritional intake and maternal age on the incidence of anemia in second-trimester pregnant women in Mojo Village, Bojonegoro Regency. This study used a quantitative design with a cross-sectional approach. The study was conducted from December 2023 to January 2024. The population and sample were all second-trimester pregnant women with anemia, totaling 30 respondents, selected using a total sampling technique. Data analysis used multiple linear regression tests. The characteristics of the respondents were mostly of healthy reproductive age 17-35 years (80%) and had secondary education (83.3%). The results of the simultaneous test showed a significant effect between nutritional intake and maternal age on the incidence of anemia. Maternal age was the most dominant variable. There was a significant effect both simultaneously and partially between pre-pregnancy nutritional intake and maternal age on the incidence of anemia in second-trimester pregnant women. Improved pre-conception nutrition education and gestational age planning are needed to prevent anemia.